Stability of structures in non-equilibrium systems - Verichev, Nikolay Nikolaevich (Computational Continuum Mechanics, 2013)
The application of lattices of lumped dynamical systems (oscillators) as alternative models for the dynamics of convective flows is considered. The stability of one- and two-dimensional main-flow structures and the stability of secondary-flow structures are studied in the context of the dynamics of lattices. Stability conditions are analyzed depending on the intensity of structural turbulence and the geometry of the structured liquid layer.